Can Deliberative Democracy Provide Remedies for Affective Polarisation? - Setälä, Maija; O'Flynn, Ian (SAGE Publications, 2025)
This article revisits the problems of electoral democracy, especially affective polarisation, from the perspective of the theory of deliberative democracy. Some authors representing ‘realist’ views of democracy have concluded that empirical findings regarding affective polarisation challenge not just the idea of representative democracy as responsive government but also the prospects for deliberative democracy. We point out certain problems and limitations in this conclusion and discuss how theories of deliberative democracy might actually help find remedies for affective polarisation. We apply a recent distinction by Hartman et al. as an intermediate-level conceptualisation that helps translate the theory of deliberative democracy into deliberative practices. To illustrate the potential of deliberative practices, we analyse how forums for citizen deliberation such as deliberative mini-publics could help counteract affective polarisation. We reflect on the strengths and weaknesses of deliberative forums from a systemic perspective.